Resilient retfærdighed? Klimabevægelsen og den systemiske retorik - Jacobsen, Stefan Gaarsmand (Slagmark - Tidsskrift for idéhistorie, 2018)
This article uses the idea of resilience as a point of departure for analysing some contemporary challenges to the climate justice movement posed by social-ecological sciences. Climate justice activists are increasingly rallying for a system-change, demanding fundamental changes to political bureaucracy and the economy, which would put ecology, biodiversity and climate change first for all future political decisions. Since the concept of resilience has taken up a central role in recent developments in ecological sciences, it has also become part of the activist debate. The article’s main argument is that the scientific framework behind resilience is not politically neutral and that this framework tends to weaken the activist’s demands for a just transition and place more emphasis on technical and bureaucratic processes.